Prosthesis - Vinjamuri, Ramana (IntechOpen, 2020)
Prosthesis is an addition or attachment to the body that replicates the function of a lost or dysfunctional limb. Prostheses have evolved over the centuries starting from wooden and metal levers to highly sophisticated robotic limbs. While the design of prostheses has become complex and multidimensional, their control methodologies have been developed using signal processing and machine learning methods. This book reports on the recent progress in the design and control of prostheses.